Analysis of the competitive activities of Ukrainian champions with the strongest fighters of world (based on world championship in Greco-Roman wrestling in 2011) - Radchenko Y.А (Kharkov National Pedagogical University, 2012)
The comparative analysis of results of competition activity of the strongest fighters is presented Greco-Roman style on a world of 2011 cup. Found out some tendencies and conformities to the law in application technical tactical actions by fighters in a competition duel on the modern stage of development to Greco-Roman fight. It is set that in most cases sportsmen won due to ability to win with insignificant advantage for all of competitors. They most adjusted to the modern requirements of conduct of duel, conduct an active fight and own effective attacking receptions, reliably they are applied and rarely attack without an estimation. One of more effective receptions in an orchestra there is defence of fighter which is down. Found out failings in preparation of the Ukrainian sportsmen can underlie correction of the programs of preparation to the Olympic games. It is recommended to utillize the resulted information for the design of the special trainings tasks which are conditioned the individual features of separate sportsmen.